2013
DOI: 10.56431/p-9fm4q6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Radiological Dose around a 3-MW TRIGA Mark-II Research Reactor

Abstract: A hypothetical accidental case of a 3-MW TRIGA Mark-II research reactor has been assumed to assess the radiological consequences due to the deposition of 137Cs and 90Sr on ground, vegetation, milk and meat. The air concentrations in sixteen cardinal directions have been estimated where the maximum concentration has been found to be at 110 m distance from the core of the reactor for all the directions. Calculated maximum doses of 137Cs, 90Sr and both 137Cs and 90Sr have been found to be within the ranges of 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The study found that 131 I contributes the most to the dose in vegetation compared to all other radionuclides. Mizanur et al [9] evaluated the radiological effects of Cs-137 and Sr-90 deposition on the ground, vegetation, milk, and meat. The study examined various pathways and air concentrations of accumulated radionuclides at the same reactor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study found that 131 I contributes the most to the dose in vegetation compared to all other radionuclides. Mizanur et al [9] evaluated the radiological effects of Cs-137 and Sr-90 deposition on the ground, vegetation, milk, and meat. The study examined various pathways and air concentrations of accumulated radionuclides at the same reactor.…”
Section: Introductionmentioning
confidence: 99%
“…We calculated the airborne fraction of these isotopes remaining to be released into the atmosphere from the 3MW(t) research reactor TRIGA Mark-II, which will be operate for 10 days. Our results were compared with some findings from the bibliography [8][9]. To elaborate on this work, we need to specify certain parameters in advance.…”
Section: Introductionmentioning
confidence: 99%